2019
DOI: 10.1111/1556-4029.14249
|View full text |Cite
|
Sign up to set email alerts
|

Application of Structured‐Light 3‐D Scanning to the Documentation of Plastic Fingerprint Impressions: A Quality Comparison with Traditional Photography

Abstract: Plastic fingerprint impressions found at crime scenes are often too delicate for collection, leaving photography as the best option for documentation. However, traditional photography techniques can be inadequate in documenting minute 3-D details due to limitations of the camera and lighting conditions. This study investigated the feasibility of applying commercially available structured-light 3-D scanners in the documentation of plastic prints. Attempts were made to develop a procedure to extract curvature fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Winkler et al 32 assessed the trueness and precision of scanners intended for scanning smaller areas (i.e., intraoral scanners), including the Artec Space Spider, and concluded that the latter was superior to the intraoral scanners. The high resolution makes it even possible to capture fingerprints accurately 33 . Nevertheless, further research has to be done with patients to compare the widely used 3dMD-system with the Artec Space Spider scanner.…”
Section: Discussionmentioning
confidence: 99%
“…Winkler et al 32 assessed the trueness and precision of scanners intended for scanning smaller areas (i.e., intraoral scanners), including the Artec Space Spider, and concluded that the latter was superior to the intraoral scanners. The high resolution makes it even possible to capture fingerprints accurately 33 . Nevertheless, further research has to be done with patients to compare the widely used 3dMD-system with the Artec Space Spider scanner.…”
Section: Discussionmentioning
confidence: 99%
“…They also report that the real accuracy of distance measurements on the scan is much lower than the one declared by the scanners' manufacturers. In a more specific domain, the authors in [9] study the utilisation of 3D scanning of fingerprint impressions as encountered on different materials compared to traditional 2D photography. They utilised two scanners, an inEos X5, which is a tabletop device, specialised for dental use, and a handheld structured light scanner (Artec Space Spider).…”
Section: Related Workmentioning
confidence: 99%
“…The study tested precision, and not trueness, because the true form of the specimens would be difficult to obtain in such high detail. However, the fact that precision was high in all different tested scenarios (various anatomical form configurations in different surface conditions), along with the established trueness of the scanner in various other models [ 16 , 18 , 19 , 20 , 21 ], strongly indicates that high accuracy would also be evident in the skeletal surfaces tested here. The high accuracy of this scanner has already been exhibited in previous studies testing different surfaces such as teeth [ 16 ], human skin [ 18 , 19 ], human fingerprints depicted in plastic materials [ 20 ], or even in difficult-to-scan objects [ 21 ].…”
Section: Discussionmentioning
confidence: 66%